TINJAUAN STRUKTUR GENETIK SERTA TINGKAT KEGANASAN VIRUS INFLUENZA H1N1 - Andrijanto Hauferson Angi (Politeknik Pertanian Negeri Kupang, 2010)
Evaluation Structure of Genetic and Virulens Influenza Virus of H1N1. Influenza of H1N1 or Mexico Flu or Pig Influenza or of Pig Flu ( Swine Influenza or Pig Flu) representing disease of acute exhalation channel (severe) caused of virus and can be catching very fast. Influenza of H1N1 resulted from by type influenza virus type A of Orthomyxoviridae family. This Virus have the character of patogen at human being, poultry, horse, and pig. Virus of Orthomyxoviridae family is particle camouflage in form of circular or domed of length, representing RNA genom enchain single by 8 segment, and also have negative polarity. Influenza of A (H1N1) represent new strain of influenza virus of A which is human being infection. Influenza of A ( H1N1) differ from other influenza virus strain which during the time often human being infection and most human being don't have impenetrability to virus. Therefore the virus can easily disseminate from human being to human being. Infection happened to through air (cough, sneezing) or direct contact with object or patient which have terkontaminasi. Infection of the virus can happened swiftly especially at young people (age 10 - 45 year). Influenza symptom of A (H1N1) is fever, cough, headache, mialgia ( muscle pain in bone), joint pain in bone, bronchitis, head cold and is sometime accompanied with diarrhoea and puking. The symptom known as by Influenza-Like Illness (ILI) or of Flu-Like syndrome because looking like symptom of flu other bronchi infection or which is often experienced of by human being. Influenza of A (H1N1) difficult differentiated with other bronchi infection or flu if only pursuant to at disease symptom.Keywords: Influenza Virus H1N1, Orthomyxoviridae.